Relatório de Estágio Profissional - Dilemas e dificuldades de um Professor Estagiário: A dimensão do Estágio Profissional - Vasco Nuno Faustino Mendes (2018)
This internship report is part of the Vocational Training Curricular Unit, inserted in the 2nd year of the 2nd cycle in Physical Education Teaching in Basic and Secondary School Levels of the Faculty of Sport of the University of Porto. This report aims to describe and reflect on my experiences during the 2016/2017 school year as Physical Education Intern Trainee in a 10th grade and a 5th grade class in the Ermesinde Secondary School, belonging to the Ermesinde School Grouping . Structurally, the report is divided into five chapters: 1) Introduction, which reports on the framework of the Professional Internship; 2) Personal Framework, in which I refer to my personal experience and expectations regarding the Professional Internship; 3) Professional Practice Framework, which includes the legal, institutional and functional framework of the Professional Internship, with a characterization of the school, the internship nucleus and the classes taught; 4) Performance of the Professional Practice in performance areas 1, 2 and 3, with area 1 referring to the design, planning, realization and evaluation processes; area 2 encompasses the activities carried out and developed in the school environment; area 3 covers the research study carried out, regarding the dimentions of didatics and the difficulties of managing the class for a trainee teacher in the 2nd cycle and in secondary; 5) Final Considerations and Future Perspectives, which includes, in the form of a conclusion, a general reflection on the professional stage, expressing the contribution of this year as trainee for the performance of the teaching profession and as a fundamental part of my formation and construction of identity, and also my perspectives on the future